PENGARUH PEMBANGUNAN APARTEMEN ARANDRA RESIDENCE TERHADAP KINERJA LALU LINTAS DI RUAS JALAN SEKITAR CEMPAKA PUTIH - Ramadhan, Muhammad; Darmadi (FTSP Universitas Jayabaya, 2024)
Traffic impact analysis needs to be done to know the traffic volume of the indicator being assessed is the traffic performance. The analysis was conducted with reference to the 1997 Indonesian Road Capacity Manual and the Contram 5 Program. The existing condition has the highest V / C Ratio 0.78 increased to 0.86, the travel time from 77.8 hours to 82 hours, the length of the trip from 3142.6 kend-km to 3307 kend-km, network speed from 40.4 km / h to 40.3 km / h, use of fuel from 305.6 liters to 312.7 liters fuel consumption from 305.6 liters to 312.7 liters, and survival of the queue in the network in the state of 0 vehicles. Related to that need to do handling.